An in-depth investigation of NAs-induced osteoporosis adverse events: a real-world, network toxicology and molecular docking analysis - Di, Jingkai; Wang, Shuang; Liu, Lujia; Qi, Likun; Guo, Zijian; Qin, Yingda; Xiang, Chuan (Frontiers in Medicine, 2025)
BackgroundNucleoside and nucleotide analogs are one of the mainstays of treatment for chronic hepatitis B, but their effects on bone density are highly controversial.MethodsIn this study, four pharmacovigilance analysis methods and Bonferroni-corrected p-values were used to analyze the FDA Adverse Event Reporting System database to investigate the relationship between adefovir and tenofovir and osteoporosine-related adverse events. In addition, the biological pathways and target proteins were studied by network toxicology and molecular docking techniques.ResultsAdefovir showed signs of adverse skeletal events at the two PT levels of OSTEOPOROSIS and BONE DENSITY DECREASED, while tenofovir showed signs of adverse skeletal events at the five PT levels of BONE DENSITY DECREASED, BONE LOSS, OSTEOPENIA, OSTEOPOROSIS and OSTEOPOROTIC FRACTURE. Furthermore, at the overall SMQ level, positive signals of adverse skeletal events were also valid. Subgroup analysis showed that adefovir was more likely to cause osteoporosis in the elderly and women, while tenofovir exhibited the opposite trend. Furthermore, GO and KEGG analyses indicated that both drugs may jointly promote osteoporosis through pathways such as cell migration, G protein-coupled receptor and Toll-like receptor signaling pathways. Molecular docking technology further reveals that the two drugs can produce pathological effects by binding to osteoporosis-related genes such as ADORA1 and JAK1.ConclusionThis study comprehensively reported the risk and mechanisms of osteoporosis caused by the clinical use of NAs drugs, and provided more detailed recommendations for clinical improvement and prevention of adverse events.